Peningkatan Pemahaman Peserta Didik Fase E Terhadap Materi Fikih Riba Menggunakan Asesmen Formatif Model Poster - Basri, Junaidin; Hikmah, Sopiatul (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
Student’s understanding of the material on riba fiqh in class X-C MAN 1 Garut is still relatively low, as evidenced by the results of the pre-cycle test with a learning completion of only 27.78%. One alternative solution to overcome this problem is to implement a poster-style formative assessment that aims to gradually improve students' understanding. This study aims to describe the increase in students' understanding of the material on riba fiqh through the implementation of a poster-style formative assessment. The study used a Classroom Action Research (CAR) approach with a cycle of planning, action, observation, and reflection. Data were collected through an understanding test reinforced by observation and document study. The results showed that the implementation of the poster-style formative assessment was able to significantly improve students' understanding, both in the aspects of knowledge, analysis, and application of the concept of riba according to the cognitive stages in Bloom's taxonomy. Learning completion increased from 27.78% in the pre-cycle to 72.22% (24 students) in cycle I and 97.22% (35 students) in cycle II from a total of 36 students. Thus, the poster model formative assessment has been proven to improve the quality of learning of riba fiqh material at MAN 1 Garut. Keywords : understanding of riba material, formative assessment, classroom action research